Penerapan Media Gambar untuk Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Penjaskes di Sekolah Dasar Negeri Mokeasa - Aschari Senjahari Rawe; Berty Sadipun (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
The objectives of this study were to determine the implementation and the effect of image media in Physical and Health Education subjects at Mokeasa State Elementary School, Ende Regency. This study employed Classroom Action Research (CAR) using a qualitative research approach. The research design applied was the Kemmis and Taggart Model. The study consisted of two cycles, namely Cycle I and Cycle II. Data collection techniques used in this study included interviews, observations, documentation, tests, and field notes. The results of the study showed an improvement in students’ learning outcomes in each cycle. In Cycle I, the average score was 68.88%, and there was a significant improvement in students’ learning outcomes in Cycle II, with an average score of 91.11%. Based on these results, it can be concluded that the implementation of image media can improve learning outcomes in healthy lifestyle culture material for fifth-grade students at Mokeasa State Elementary School, Ende Regency. Keywords: Learning Outcomes, Image Media, Physical Education